P-clean rings - Weixing Chen (International Journal of Mathematics and Mathematical Sciences)
In this paper we unify the structures of various clean rings by introducing the notion of P-clean rings. Some properties of P-clean rings are investigated, which generalize the known results on clean rings, semiclean rings, n-clean rings, and so forth. By the way, we answer a question of Xiao and Tong on n-clean rings in the negative.